Qualitative research interview challenges. Experience report - Oliveira, Stefanie Griebeler; Quintana, Alberto Manuel; Budó, Maria de Lourdes Denardin; Lüdtke, Manoela Fonseca; Cassel, Paula Argemi; Garcia, Raquel Pötter (Investigación y Educación en Enfermería, 2011)
Report of the perceptions emerged from the experience of the qualitative research “Representações Sociais da Internação Domiciliar na terminalidade: o olhar do cuidador familiar” data collection. Difficulties for the researcher in performing the interviews, especially in establishing a horizontal relationship between the researcher and the researched, are shown.